2001
DOI: 10.1073/pnas.131188498
|View full text |Cite
|
Sign up to set email alerts
|

Human tumor suppressor EXT gene family members EXTL1 and EXTL3 encode α1,4- N -acetylglucosaminyltransferases that likely are involved in heparan sulfate/ heparin biosynthesis

Abstract: The tumor suppressors EXT1 and EXT2 are associated with hereditary multiple exostoses and encode bifunctional glycosyltransferases essential for chain polymerization of heparan sulfate (HS) and its analog, heparin (Hep). Three highly homologous EXT-like genes, EXTL1-EXTL3, have been cloned, and EXTL2 is an ␣1,4-GlcNAc transferase I, the key enzyme that initiates the HS͞Hep synthesis. In the present study, truncated forms of EXTL1 and EXTL3, lacking the putative NH 2-terminal transmembrane and cytoplasmic domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 51 publications
1
144
1
Order By: Relevance
“…Identification of EXTL2 as GlcNAcT-I for HS/heparin synthesis suggested that other EXT-like genes also have some roles in HS formation. In fact, we demonstrated that EXTL1 possesses only the GlcNAcT-II activity whereas EXTL3 shows both GlcNAcT-I and -II activities (56). Neither EXTL1 nor EXTL3 show any glucuronyltransferase activity as examined with N -acetylheparosan oligosaccharides as acceptors.…”
Section: Initiation and Synthesis Of The Repeating Disaccharide Regiomentioning
confidence: 75%
“…Identification of EXTL2 as GlcNAcT-I for HS/heparin synthesis suggested that other EXT-like genes also have some roles in HS formation. In fact, we demonstrated that EXTL1 possesses only the GlcNAcT-II activity whereas EXTL3 shows both GlcNAcT-I and -II activities (56). Neither EXTL1 nor EXTL3 show any glucuronyltransferase activity as examined with N -acetylheparosan oligosaccharides as acceptors.…”
Section: Initiation and Synthesis Of The Repeating Disaccharide Regiomentioning
confidence: 75%
“…So far no additional GlcA transferases involved in actual HS chain elongation are known. Both EXTL1 and EXTL3 have been shown to be able to transfer GlcNAc (but not GlcA) to K5 oligosaccharide acceptors and are likely to be involved in HS biosynthesis (14). Of the two, only EXTL3 is ubiquitously expressed in human tissues (27,28) and therefore more likely to be part of a universal HS chain-elongating complex.…”
Section: Figmentioning
confidence: 99%
“…The EXTL genes have not been linked to hereditary multiple extoses but belong to the EXT family of proteins based on amino acid sequence similarity to EXT1 and EXT2. All three EXTL proteins express glycosyltransferase activities related to HS biosynthesis; however, their role in HS formation in vivo remains undefined (13,14).…”
mentioning
confidence: 99%
“…Members of the ADAM protein family have been implicated in cell-cell and cell-matrix interactions (Primakoff and Myles, 2000). EXTL3 is a member of the exostosis (EXT) gene family, which has been tightly associated with glycosyltransferase activities required for the biosynthesis of heparin sulfate (Kim et al, 2001). For two members of the EXT-family, EXT1 and EXT2, a TSG function has been postulated.…”
Section: Discussionmentioning
confidence: 99%